Smart Street Solutions Using Iot - Ganesh Kumar, E; Anusha, Kandhadai; Saipriya, V; Dass, P (International Journal of Engineering and Technology, 2018)
Street light failure has become a major problem in cities nowadays. As the failure reports are sent very rare to government, these failures are checked only if a higher involvement action takes place. Monitoring of street lights and controlling is of utmost importance in developing country like India. Moreover, in todayâ€™s world, power saving is very important and difficult. Though there are many power generation methods, it has become very difficult due to insufficient resources. Considering this as a problem, this project is developed to send accurate location of fuse blown street light to a contact number (if government number provided). When a Street light doesnâ€™t glow even after it is powered ON, the light detector circuit detects which is immediately sent to an IntelÂ® Edison processor which processes the information. A GSM Module is attached to it, which sends the location of the blown fuse street light to the respective contact number. Â Â